PENGENDALIAN KASUS TUBERKULOSIS MELALUI KELOMPOK KADER PEDULI TB (KKP-TB) - Ni Luh Putu Eva Yanti (Coping: Community of Publishing in Nursing, 2016)
The tuberculosis control program can be done through support groups. Support group is a group of social people or professional to support TB patients and family to adhere of treatment and prevention of TB transmission. Support groups tuberculosis involving health volunteer in community is called Kelompok Kader Peduli TB (KKP-TB). The purpose of research is to identify the ability of knowledge, attitudes, and skills of KKP-TB in TB control program. The results showed an increase in knowledge, attitudes, and skills of KKP-TB in controlling TB. Kelompok Kader Peduli TB can strengthen TB control programs in the community.